2010
DOI: 10.1007/s00438-010-0565-0
|View full text |Cite
|
Sign up to set email alerts
|

Antler development and coupled osteoporosis in the skeleton of red deer Cervus elaphus: expression dynamics for regulatory and effector genes

Abstract: Antlers of deer display the fastest and most robust bone development in the animal kingdom. Deposition of the minerals in the cartilage preceding ossification is a specific feature of the developing antler. We have cloned 28 genes which are upregulated in the cartilaginous section (called mineralized cartilage) of the developing ("velvet") antler of red deer stags, compared to their levels in the fetal cartilage. Fifteen of these genes were further characterized by their expression pattern along the tissue zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Therefore, proteomic studies on deer followed a cross-species strategy, using a given protein database of other sequenced organism with close relative genome, analogous to the proteome profiling of Pedobacter cryoconitis [20], L. starkeyi [21] and Marenzelleria [22]. Since deer and bovine are very closely related in phylogenetics [23,24], the gene sequences of cow show high similarity (in the range 90-99%) with deer genes in the coding regions of mRNAs [25,26]. Similarly, some reports on gene expression in deer antler also revealed that the deer genes all showed high sequence homology (above 90%) to that of bovine [5,27].…”
Section: Methods Development For Efficient Protein Extractionmentioning
confidence: 99%
“…Therefore, proteomic studies on deer followed a cross-species strategy, using a given protein database of other sequenced organism with close relative genome, analogous to the proteome profiling of Pedobacter cryoconitis [20], L. starkeyi [21] and Marenzelleria [22]. Since deer and bovine are very closely related in phylogenetics [23,24], the gene sequences of cow show high similarity (in the range 90-99%) with deer genes in the coding regions of mRNAs [25,26]. Similarly, some reports on gene expression in deer antler also revealed that the deer genes all showed high sequence homology (above 90%) to that of bovine [5,27].…”
Section: Methods Development For Efficient Protein Extractionmentioning
confidence: 99%
“…The development of antlers is a modified endochondral ossification process (Rucklidge et al, 1997). The growth rate of the antler may reach over 100 g per day between May and July (on the northern hemisphere), enormous bone mass (generally 7-9 kg, occaisionally 13-15 kg, as reported from the Danube-Drava-Gemenc-Bilje Park of Nature in Hungary and Croatia) develops within 120-150 days (Stéger et al, 2010). At the end of the antler growing period the hard bony antler is the trophy.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative genomic approaches represent successful strategies to explore the genes and gene networks behind an interesting biological phenomenon. For example, several candidate genes behind human osteoporosis were revealed by comparing the transcriptomes of red deer (Cervus elaphus) osteoporotic and regenerating rib bone samples [4,5]. In the present study we followed the experimental strategy above, and made use of the plaque-based competitive hybridization (PBCH) technique which was successfully used to identify e.g.…”
Section: Introductionmentioning
confidence: 99%
“…the genes regulating red deer antler development [6]. The PBCH technique is an alternative method to procedures such as applied fragment *Address correspondence to this author at the University of Szeged, Faculty of Medicine, Department of Biology, H-6720 Szeged, Somogyi Street 4, Hungary; Tel: +36 62 545108; Fax: +36 62 545131; E-mail: villanyi22@gmail.com length comparisons and DNA chip technology to identify differentially expressed genes [5][6][7][8]. In the present study we compared transcriptomes by analyzing about 600,000 cDNA clones from both the courting and caring zebra finch male brain libraries using the PBCH method.…”
Section: Introductionmentioning
confidence: 99%